Experience in the use of seismic recording of vibrations from trains to evaluate the condition of buildings and structures - N. K. Kapustyan; G. N. Antonovskaya; I. M. Basakina (Вестник Научно-исследовательского института железнодорожного транспорта)
Constructions along railway traffic lines are always exposed to vinrations generated by the passing transport. This sometimes leads to shifts in their state even threatening the comfort of the people that stay here. To estimate the magnitude of such effect one needs the frequency-amplitude chart of impacting vibrations. Current codes [1] are applied to the main types of buildings and state the acceptable level of magnitudes in wide frequency ranges. However, the code’s regulations are not enough to ensure the building’s stability as the real state of this building is not taken into account. This is especially true for the historical buildings near railroads. Majority of these are cult-related and are mostly damaged and need renovation. To correctly estimate an impact of vibrations one needs to measure addition tensions due to vibration in the construction’s body and to compare them with ones resistance material calculations. In other words, seismic vibrations emitted by trains act as a seismic signal, for which there are several established methods of evaluation. Finite elements simulations enables estimation of the distribution of static and dynamic loads so that the most vulnerable locations in the construction’s body are identified. Consequently the simulation can use experimentally recorded waves (spectra or accelerogramms) as the dynamic load. With the simulation stage set different model types are cycled until the satisfactory match is obtained as is shown in the paper. Importantly, we demonstrate how construction evaluation methods can be combined with applied seismic methods, which are being actively developed for the needs of soil and construction integrity evaluations.